Prevalence of Depressive Symptoms among Thai Reproductive-Aged Woman with Polycystic Ovary Syndrome and Associated Factors - Achavangkool, Thanaree; Wongwananuruk, Thanyarat; Hataiyusuk, Somboon; Chantrapnichkul, Panicha; Indhavivadhana, Suchada; Tanmahasamut, Prasong; Rattanachaiyanont, Manee; Techatraisak, Kitirat; Angsuwathana, Surasak; Sanga-areekul, Nutchaya (Thai Journal of Obstetrics and Gynaecology, 2024)
Objectives: This study aimed to determine the prevalence of depressive symptoms among Thai reproductive-aged woman with polycystic ovary syndrome (PCOS) and to identify factors associated with depression in this population. Materials and Methods: A cross-sectional, questionnaire-based study was conducted at the Gynecologic Endocrinology Unit of Siriraj Hospital. The study enrolled women with PCOS between February 2022 and April 2023. The women were aged 18-45 years and met the revised Rotterdam 2003 criteria for PCOS. Participants with a prior psychiatric diagnosis or history of psychiatric medication use were excluded. Information was gathered about their background and recorded signs and symptoms of PCOS. The Patient Health Questionnaire-9 (PHQ-9) was used to assess depression and its severity. This study, scores of 9 or more indicated depressive disorder. Results: A total of 193 PCOS women participated, with a mean age of 26.1 ± 5.4 years. Most participants exhibited oligomenorrhea (96.9%) and hyperandrogenism (93.8%). The prevalence of depression was 39.9%, with severity categorized as mild (28.0%), moderate (11.4%), and severe (0.5%). Univariate analysis identified that being a student, having no savings from income, the presence of acanthosis nigricans, and hyperandrogenism were significantly associated with depression. Multiple logistic regression analysis further revealed that only the absence of savings was significantly associated with depression in this population. Conclusion: The prevalence of depression in Thai PCOS women, as categorized by the PHQ-9, was 39.9%. A lack of savings from income was a significant factor associated with depression in Thai reproductive women with PCOS.